1988
DOI: 10.1148/radiology.167.3.3363137
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloarthropathy from long-term hemodialysis.

Abstract: Twenty-six patients undergoing long-term hemodialysis who had hand and wrist abnormalities were examined for the presence of concurrent spinal disease. Six patients (23%) were found to have spinal disease on radiographs. In four, the findings resembled those of a destructive spondyloarthropathy, and in two, a less destructive erosive arthritis. A review of the spinal radiographs of 31 patients with normal hands and wrists revealed no such abnormalities. Postmortem examinations of two patients with spondyloarth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
4

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 0 publications
1
26
0
4
Order By: Relevance
“…A chronic arthropathy that predominantly involves the shoulders and is frequently associated with amyloid carpal tunnel syndrome (CTS), subchondral bone cysts or erosions, and destructive arthropathies has recently been described in such patients (2). The cervical spine is frequently involved in this erosive process, and there are numerous reports of a destructive spondylarthropathy of the cervical spine (3)(4)(5)(6)(7)(8)(9)(10). However, the craniovertebral junction has not been extensively investigated, despite the risk of severe neurologic complications associated with lesions at this site.…”
mentioning
confidence: 99%
“…A chronic arthropathy that predominantly involves the shoulders and is frequently associated with amyloid carpal tunnel syndrome (CTS), subchondral bone cysts or erosions, and destructive arthropathies has recently been described in such patients (2). The cervical spine is frequently involved in this erosive process, and there are numerous reports of a destructive spondylarthropathy of the cervical spine (3)(4)(5)(6)(7)(8)(9)(10). However, the craniovertebral junction has not been extensively investigated, despite the risk of severe neurologic complications associated with lesions at this site.…”
mentioning
confidence: 99%
“…17,18 Mechanical factors also seem to be important, as the disease predominantly affects the most mobile segments of both the cervical and the lumbar spine. 1,3,[19][20][21] One of the biologic characteristics of ␤2-microglobulin is a strong affinity to collagen fibers. 6,22,23 Ohashi et al 6 reported a possible relationship between disc degeneration and deposition of ␤2-microglobulin and stated as their opinion that quantitative and qualitative changes of collagen and glycosaminoglycan in the degenerative discs were the main factors enhancing the affinity of ␤2-microglobulin to the discs.…”
Section: Discussionmentioning
confidence: 99%
“…A second form is more destructive, with bone fragmentation and soft tissue involvement [38,39]. A third form can present with erosions and/or destructive changes of the intervertebral disc space [40], Destructive spondylarthropathy has also been noted in uremic patients prior to the onset of hemodialysis as well as in patients treated with peritoneal dialysis [5,[41][42][43][44], While it was initially assumed that destructive spondy larthropathy in long-term hemodialysis patients was due to the deposition of hydroxyapatite crystals [37], it may also be associated with other clinical problems, including hyperparathyroidism, AP2M amyloid deposition, and alu minium intoxication [45]. Furthermore, it should be kept in mind that age-associated amyloid deposits that are unrelated to AP2M type amyloid may be found in inter vertebral discs and articular cartilage [46,47], The role of AP2M amyloid, however, in the pathogenesis of spondyl arthropathy has been emphasized by Sebert et al [48] and recently AP2M deposits, located preferentially in cervical discs, were demonstrated in a large series of renal failure autopsy cases [49].…”
Section: Spondylarthropathymentioning
confidence: 99%